Status and outlook for lithium-ion battery cathode material synthesis and the application of mechanistic modeling. (1st April 2023) - Pardikar, Kunal; Entwistle, Jake; Ge, Ruihuan; Cumming, Denis; Smith, Rachel
Abstract: This work reviews different techniques available for the synthesis and modification of cathode active material (CAM) particles used in Li-ion batteries. The synthesis techniques are analyzed in terms of processes involved and product particle structure. The knowledge gap in the process-particle structure relationship is identified. Many of these processes are employed in other similar industries; hence, parallel insights and knowledge transfer can be applied to battery materials. Here, we discuss examples of applications of different mechanistic models outside the battery literature and identify similar potential applications for the synthesis of CAMs. We propose that the widespread implementation of such mechanistic models will increase the understanding of the process-particle structure relationship. Such understanding will provide better control over the CAM synthesis technique and open doors to the precise tailoring of product particle morphologies favorable for enhanced electrochemical performance.